Sanitized, IMCD Brasil link up for polymer specialty chemicals; new US headquarters for IMCD. Issue 12 (December 2020) - Unknown
Abstract : Swiss-based antimicrobial hygiene company Sanitized is partnering with IMCD Brasil, the Brazilian business of the Dutch-based international specialty chemicals distributor, to design value-added products for the polymer industry and optimize their use in innovative and customer-specific solutions.